2012
DOI: 10.1103/physreve.86.036211
|View full text |Cite
|
Sign up to set email alerts
|

Motion of rotating pairs in a hexagonal superlattice pattern within dielectric barrier discharge

Abstract: Stochastic rotation of rotating pairs in a hexagonal superlattice pattern is observed in a dielectric barrier discharge system. It is found that the pairs rotate with orientation and diameter randomly changing by observing a series of frames recorded by a high speed video camera. Frames recorded by a high speed framing camera with an exposure time corresponding to current pulse phases in one half cycle of the applied voltage show that one rotating spot, six small spots, and another rotating spot in one cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Sometimes only a slight change in one controlling parameter may result in a significant change in the DBD patterns. In some cases, patterns can rotate [26,36,37], move [38,39], collide and scatter [40][41][42][43], form spiral and chaos [44], and some other collective effects [34,45], even if the discharge conditions are kept.…”
Section: Status Of Patterns In Dbdmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes only a slight change in one controlling parameter may result in a significant change in the DBD patterns. In some cases, patterns can rotate [26,36,37], move [38,39], collide and scatter [40][41][42][43], form spiral and chaos [44], and some other collective effects [34,45], even if the discharge conditions are kept.…”
Section: Status Of Patterns In Dbdmentioning
confidence: 99%
“…The patterns in various states can self-organize into hexagons, squares, rings and stripes. Mixtures of simple structures of DBD can form some complex patterns like honeycomb, superlattice, etc[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Figures2 and 3show a collection of stable DBD patterns obtained by different research groups.…”
mentioning
confidence: 99%
“…It can be concluded that the moving mode of the moving filaments is antisymmetric stretching vibration, which is similar to the vibration mode of isolated particles in dust plasma. [24] It is worth pointing out that the antisymmetric stretching vibration of the vibrating filaments is a kind of collective vibration.…”
Section: Resultsmentioning
confidence: 99%
“…During recent years, more and more dynamic patterns have been discovered and studied. [23,24] Generally, the pattern consists of several sets of sublattices, and the latter sublattices are discharged at the center of the last sub-lattice. For instance, Cui et al observed a honeycomb pattern with moving filaments, and the central spots were discharged at the centers of the hexagons formed by the moving filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes only a slight change in one controlling parameter may result in a significant change in the DBD patterns. In some cases, patterns can rotate [30,31], move [32], collide and scatter [33,34], form spirals and chaos [35], and some other collective effects [36], even if the discharge conditions are kept. All of these investigations promote a deep understanding of the mechanism of the DBD discharge.…”
Section: Introductionmentioning
confidence: 99%